2018
DOI: 10.1080/10803548.2017.1389464
|View full text |Cite
|
Sign up to set email alerts
|

Influence of visual clutter on the effect of navigated safety inspection: a case study on elevator installation

Abstract: The effect of a strengthened working memory on the detection rate through increased search efficiency is more apparent in high visual clutter. This study confirms the role of visual clutter in construction-navigated inspections, thus serving as a foundation for the optimization of inspection planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…It should be noted that eight studies (accounting for 36%) excluded some participants, and the average rejection rate is about 22%. Invalid participants are rejected for a variety of reasons such as unacceptable levels of calibration on the eye tracker ( Hasanzadeh et al, 2017a , b , 2018 ; Hasanzadeh et al, 2019 ), univariate outliers ( Hasanzadeh et al, 2017a ), interruptions during eye-tracking experiments ( Hasanzadeh et al, 2017a ), abnormal or incorrectible-to-normal vision ( Park et al, 2022 ), failures in pre-experiments ( Liao et al, 2019 ; Sun et al, 2020 ), and uncooperative participants ( Cheng et al, 2021 ; Park et al, 2022 ). This indicates that to ensure the sufficient experiment size of participants, the researchers should recruit more participants as appropriate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that eight studies (accounting for 36%) excluded some participants, and the average rejection rate is about 22%. Invalid participants are rejected for a variety of reasons such as unacceptable levels of calibration on the eye tracker ( Hasanzadeh et al, 2017a , b , 2018 ; Hasanzadeh et al, 2019 ), univariate outliers ( Hasanzadeh et al, 2017a ), interruptions during eye-tracking experiments ( Hasanzadeh et al, 2017a ), abnormal or incorrectible-to-normal vision ( Park et al, 2022 ), failures in pre-experiments ( Liao et al, 2019 ; Sun et al, 2020 ), and uncooperative participants ( Cheng et al, 2021 ; Park et al, 2022 ). This indicates that to ensure the sufficient experiment size of participants, the researchers should recruit more participants as appropriate.…”
Section: Resultsmentioning
confidence: 99%
“…However, Jeelani et al (2019) indicated that participants with better recognition performance spent more time on each hazard. Liao et al (2019) believed that there is no clear correlation between hazard recognition accuracy and fixation time. Conclusions from these studies are different and even conflicting.…”
Section: Resultsmentioning
confidence: 99%
“…Navigated inspection offers search templates of hazards in the inspector's working memory by looking through a checklist before inspection, serving as a top-down guidance for selective attention [28,29]. The guidance from the working memory can quickly focus selective attention on relevant targets rather than background images [30,31].…”
Section: Experience and Working Memory Are The Two Critical Factors Tmentioning
confidence: 99%
“…Yet, there is another guidance mechanism, which relates to looking at the outstanding features of targets, which can be identified from differences in luminance, color, motion, orientation, or size between items [32,33]. It was shown that a contrast in at least one dimension between an object and its background can capture an observer's attention [29]. The search ability is affected by both top-down and bottom-up patterns [34].…”
Section: Vc Serves As a Potential Classifier For Navigated Inspectionmentioning
confidence: 99%
See 1 more Smart Citation